MEDIA PEMBELAJARAN PENGENALAN BUDAYA PAPUA BERBASIS WEBSITE - Agustin Setyorini (Informasi Interaktif, 2017)
Papua Province is a province that is still thick and rich in arts and culture that exist in the province, this province has various tribes such as tribe asmat who menghiamin the province, with a society that highly uphold the arts and culture that exist in their area. The arts and culture that exist in this area is very interesting, and unique. Advances in technology today, can be perceived benefits in various fields, such as making learning media that can facilitate us in learning something. In general, media that can be used to learn the language of children is the visual media and audio media. Advancement of technology today is so fast that we can access various information via the internet. To learn Indonesian culture we also easily get information from the Internet. One way of learning through the internet is web-based learning. Web-based learning is a learning activity that utilizes the media sites (websites) that can be accessed through the Internet network. Web-based learning or also known as "web based learning" is one type of application of electronic learning (e-learning). The purpose of this research is to design and design a learning media to recognize the culture of Papua. This research is expected to facilitate the user to be more familiar with Papuan cultural diversity.Key words: Media Learning, Culture, Papua, Website.